Social media and digital politics : networked reason in an age of digital emotion - Lee, James Jaehoon; Blevins, Jeffrey Layne (New York : Routledge, 2025)
"Informed by critical theory, this book employs Social Network Analysis (SNA) to examine the ever-increasing impact that social media has on politics and contemporary civic discourse. In just the past decade social media platforms have been at the forefront of political discord that played out in the January 6th insurrection, the expulsion of a U.S. President from major social media platforms, the attempted regulation of social media in various states, and the takeover of Twitter (now "X") by one of the richest and (arguably) most financially influential persons in the world. This book examines these phenomena through a comprehensive and in-depth exploration of their meaning and implication for democratic society. Informed by SNA, James Jaehoon Lee and Jeffrey Layne Blevins examine several types of social and political commentary on one of the most influential social media networks and argue that the use of emotional appeals in these posts about social and political topics degrades the quality of civic discourse and encourages the abandonment of reasoning in democratic self-governance. A timely and vital text for upper-level students and scholars in a variety of disciplines from media and communication studies, journalism, digital humanities to social network analysis, political science, and sociology. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license"--
Includes bibliographical references and index.
Keywords: Online social networks -- Political activity -- 21st century; Political participation -- Technological innovations -- United States; Communication in politics -- Technological innovations -- United States; Internet and activism -- United States; Social networks -- Research